Mediating Role of Organizational Change Readiness on Knowledge Management and Entrepreneurial Orientation for Innovation - Sudhartio, Lily; Peranginangin, Pulung; Hamsal, Mohammad; Ganiarsa, Kasandika (Bina Nusantara University, 2023)
The research aimed to explore factors that could help schools enhance their innovation which is challenging due to their institution nature. Three variables were investigated as the antecedents of innovations: entrepreneurial orientation, knowledge management, and organizational change readiness. In education, entrepreneurial orientation was gauged through five dimensions: innovativeness, proactiveness, risk-taking, autonomy, and competitive aggressiveness. The knowledge management process involved three dimensions: knowledge creation, knowledge sharing, and knowledge utilization. The relationship between knowledge management variables was formative, as no single dimension fully captured the entire process; each contributes uniquely. Organizational change readiness dimensions included changing commitment and change efficacy. Dependent variable innovation was assessed through technical, administrative, and managerial innovation. The empirical research was quantitative by design, and data were collected from 110 private secondary schools across Indonesia. The research model was tested using partial least squares – structural equation modeling (PLS-SEM) with the extended repeated indicator approach. The research finds that entrepreneurial orientation does not directly affect innovation, but it is fully mediated by organizational change readiness. Additionally, while knowledge management has a significant direct effect on innovation, organizational change readiness partially mediates the relationship. The research also highlights the importance of organizational change readiness, which has rarely been discussed in entrepreneurial orientation and knowledge management literature.